(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluation of the relationship and prognostic value of 28-day mortality of lactate/albumin ratio and lactate/albumin × age score with SOFA and APACHE II scores in patients with postoperative septic shock. Subjects and methods: Cross-sectional study of 117 patients with postoperative septic shock treated at the Center for Anesthesia and Surgical Resuscitation, Viet Duc University Hospital , enrolled from June 2024 to April 2025. Results: The study analyzed 117 patients and found that the lactate/albumin ratio was similar between sexes, infection site, ASA, and age group. Lactate/albumin and lactate/albumin × age points have homologous correlation with lactate, SOFA, APACHE II and inverse with albumin. Multivariate logistic regression analysis was used, which showed that lactate/albumin ratio ≥ 0.16 was independent risk factors for 28-day mortality in postoperative septic shock patients. The predictive values ​​of lactate/albumin ratio, SOFA and APACHE II were similar and there was no significant difference between groups with the cutoff value of lactate/albumin ratio = 0.16 with a sensitivity of 91% and a specificity of 78%. The value of the lactate/albumin ratio × age score had the highest predictive value for 28-day mortality in postoperative septic shock patients. Lactate also had a good predictive value for mortality while the albumin value had no predictive value. Conclusion: Lactate/albumin index is an independent mortality risk factor with a predictive value of 28-day mortality in septic shock after surgery, with a prognostic value equivalent to SOFA and APACHE II indexes. Lactate/albumin index × age score has an even better prognostic value in predicting 28-day mortality in patients with septic shock after surgical surgery.